On the traction problem in mechanics - Malaspina, A. (Archives of Mechanics, 2005)
In this paper, we show how to solve the traction problem for the Lamé and Stokes systems by means of a double layer potential. In this way we complete the results of [5], where Cialdea and Hsiao, employing a method introduced by the first author in [1], solve the Dirichlet problem for Lamé and Stokes systems by means of a simple layer potential.